Program uor Empowering the Role of Religious Leaders as Renewal Agents for Community Health in the Covid-19 Pandemic - Oktovina Mobalen; Elisabeth Samaran; Laurdes Situmorang (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2023)
ABSTRACT The handling of Covid-19 cases must be carried out with the support of all parties, not only the responsibility of health workers because Covid-19 is a public health problem. The role of religious leaders is increasingly significant in the era of advances in information technology. The ease of influence and the role of religious leaders in controlling change significantly influence society. The primary purpose of community service activities for religious leaders is to act as an agent of health reform in the community during the Covid-19 Pandemic. This method of community service is socialization, training, and advocacy of the approach through the department of religion, and empowerment of religious leaders in the Sorong City area, Masimsa sub-district. Giving pocketbooks. The Role of Religious Leaders as Agents of Reform for Health in the Community During the Covid-19 Pandemic. Providing pocketbooks. On Empowering the Role of Religious Leaders as Agents of Reform for Health in the Community in the Covid-19 Pandemic in 2022 "Providing public health information during the Covid-19 Pandemic and what role religious leaders must play as agents of health reform in the community. Discussion with religious leaders about their understanding of health information for religious leaders. Explain the method used (e.g., counseling, training, mentoring, and others), State the number of participants, and Explain the PKM steps and implementation steps. The training method uses role-playing by providing health information to the congregation/people in the neighborhood or worship area. This activity was carried out from June to October 2022, with the target group of 50 people being religious leaders in the Malasimsa sub-district, East Sorong district, Sorong city, under the guidance of the Malasimsa Health Center. Behavioral results obtained more pre-test scores with a level of understanding of less as much as 40, enough of as much as 48%, and Good as much as 12%, while Table 4.2 level of understanding Post Test after being given a pocketbook, health education was carried out on the Covid 19 pandemic and training with methods playing a role, the results obtained are more good levels of understanding (94%) and at least less (0%), so it can be concluded that there is a difference in the results of pre-test behavior with post-test behavior. Community service results can improve the behavior of religious leaders as agents of Covid-19 renewal. Providing Pocket Books, Health Education, and training on role-playing methods are very important in increasing the role of religious leaders. Religious leaders and religious people play an essential role in public health to become agents of change in health problems in the community by providing health information to the public. Religious administrators / Daily implementation of congregational assemblies help prepare infrastructure suggestions to support the implementation of health protocols and become an example in improving public health during the Covid-19 pandemic. Keywords: Religious Leader,Ccovid-19, Reform, Health Education